Microwave-assisted synthesis of ZnO/TiO2/Ag nanocomposites as alternative antimicrobials / Priyadarshini Sakthi Mohan - Priyadarshini , Sakthi Mohan (2021)
In the present study, antimicrobial metal and metal oxide nanomaterials were synthesised using aqueous extracts of the medicinal plants, Cissus quadrangularis stem (CQS) and Morinda citrifolia (MCF) fruit. Two different sizes (15.9 nm, 24.2 nm) of silver/silver chloride nanoparticles (Ag/AgClNPs) were synthesised using CQS extract under microwave irradiation. Titanium oxide nanoparticles (TiO2NPs) were also synthesised by microwave irradiation of CQS extract followed by calcination at 450°C for 3 h. The synthesised nanoparticles were characterised by Fourier-transform infrared spectroscopy, X-ray diffraction analysis, high-resolution transmission electron microscopy and zeta potential analysis. The bioactivities of 15.9 nm, 24.2 nm Ag/AgClNPs and TiO2NPs against human nosocomial Gram-positive and Gram-negative bacterial pathogens (Pseudomonas aeruginosa ATCC 27853, Staphylococcus aureus NCTC 6571, Bacillus subtilis ATCC 23857, and Escherichia coli ATCC 25922) in liquid media were analysed. The antibacterial study results demonstrated higher bactericidal activity of Ag/AgClNPs and negligible activity of TiO2NPs against human nosocomial pathogens. Further, metabolic activity and confocal viability assay results provided strong evidence that the 15.9 nm Ag/AgClNPs inhibited the bacterial pathogens better than the 24.2 nm Ag/AgClNPs and TiO2NPs. The bioactivity of TiO2NPs was enhanced under ultraviolet (UV) illumination where it showed significant bactericidal activity of tested bacterial pathogens under UV, (365 nm) light. Photoactivation generated holes (h+) and electrons (e−) on the surface of the TiO2NPs, inducing hydroxyl (•OH) and superoxide free radicals (O2−•) reactive oxygen species (ROS) on the bacterial surface. The cytotoxicities of the synthesised Ag/AgClNPs and TiO2NPs were studied towards human A549 adenocarcinomic alveolar basal epithelial cell line and RAW 264.7 macrophage cells. Anticancer activity of both 15.9 nm Ag/AgClNPs and 24.2 nm Ag/AgClNPs displayed the IC50 values at 85 μg/mL and 90 μg/mL against A549 lung cancer cell lines while RAW 264.7 macrophage cells expressed the IC50 values at 130 μg/mL and 140 μg/mL respectively. Our results suggested that the synthesised Ag/AgClNPs can be used to develop novel antimicrobial and anticancer formulations. Secondly, for the first time, successful fabrication of ternary ZnO/TiO2/Ag nanocomposites (NCs) consisting of zinc oxide (ZnO), titanium oxide (TiO2) and silver (Ag) nanoparticles (NPs) was achieved using MCF extract and their respective precursor solutions under microwave irradiation. This ternary NCs material demonstrated enhanced bactericidal effect towards the nosocomial bacterial pathogens compared to the binary TiO2/Ag, Ag and TiO2 alone. In-vitro cytotoxicity results of the synthesised ZnO/TiO2/AgNCs on RAW 264.7 macrophages and A549 cell lines revealed a negative role in cytotoxicity but contributed astoundingly towards antimicrobials as compared to Ag alone and binary Ag/TiO2. This study shows that the resultant ternary metal/bi-semiconductor NC may provide a therapeutic strategy for eradicating bacterial pathogens without affecting the healthy mammalian cells. Lastly, the comparative study of the synthesised NPs and NCs was carried out. The results suggested that the ZnO/TiO2/AgNCs synthesised using MCF extract possessed more significant antibacterial activity and high biocompatibility than the AgNPs, Ag/AgClNPs, TiO2NPs, TiO2/AgNCs.